(untitled) (Research, Society and Development, 2023)
Orofacial harmonization plays a key role in addressing functional changes in the face and mouth, aiming to restore functionality and biomechanical balance to improve the patient’s quality of life. In addition to treating aesthetic problems, orofacial harmonization brings functional benefits to the masticatory, respiratory and vocal systems. On the other hand, bruxism, characterized by grinding or clenching of the teeth, can lead to serious consequences for the oral and general health of the individual, such as intense pain and wear on the teeth. Botulinum toxin has been widely used as an adjuvant treatment in these cases, relaxing the masticatory muscles, especially the masseter, providing pain relief. The safe and effective application of botulinum toxin in this context is paramount and, in this sense, the expertise in orofacial harmonization stands out by providing a personalized approach for each patient, making this combination a promising and minimally invasive option in the treatment of bruxism and its negative effects. . Thus, the objective of this narrative review of the literature is to comprehensively analyze the scientific evidence available on the use of botulinum toxin as an adjuvant treatment in bruxism.